Comments from the Chalkface Margins: Teachers’ Experiences with a Language Standard, Canadian Language Benchmarks - Desyatova, Yuliya (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée)

(untitled) (University of New Brunswick, 2020)
While the Canadian Language Benchmarks (CLB) document has been a milestone in supporting the teaching of English as an additional language to adults in Canada, few studies examined practitioners’ experiences with the language standard. The expectation of ongoing use of the CLB by teachers in the Language Instruction for Newcomers to Canada (LINC) program became a rigid requirement with the implementation of portfolio-based language assessment (PBLA). However, the CLB-related literature has been mostly conceptual and aspirational, while practitioners’ voices have been on the margins of research and policy making. This article examines teacher comments on the CLB, as collected during a large mixed-methods exploratory project on PBLA implementation (Desyatova, 2018, 2020). While some practitioners appreciated the standard and its impact, the majority of comments reflected comprehensibility and interpretation challenges, experienced by both teachers and learners. These challenges were further aggravated by the pressures of PBLA as a mandatory assessment protocol.